1991
DOI: 10.1259/0007-1285-64-762-555
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of intramedullary tuberculomas by magnetic resonance imaging: a report of two cases

Abstract: Intramedullary tuberculomas are rare (Arseni & Samitca, 1960; Dastur, 1972; Compton & Dorsch, 1984) but have been demonstrated either at surgery or at autopsy. The appearance of tuberculomas in the brain on magnetic resonance imaging (MRI) has been reported (Gupta et al, 1988). However, the image morphology of intrinsic cord tuberculomas has not been described. We present the MR findings in two patients with tuberculomas of the cervical cord diagnosed on the basis of positive therapeutic response to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 9 publications
2
41
1
Order By: Relevance
“…Desai [1] had reported an extradural granuloma in 6/24 (25%) cases. Dhammi et al [31] and Jena et al [32] reported intramedullary granuloma in tubercular spine which resolved on ATT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desai [1] had reported an extradural granuloma in 6/24 (25%) cases. Dhammi et al [31] and Jena et al [32] reported intramedullary granuloma in tubercular spine which resolved on ATT.…”
Section: Discussionmentioning
confidence: 99%
“…Other series have also reported almost 100% incidence of marrow oedema in cases of TB spine [1][2][3][4][5][6][7][8][9][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The caseous exudative type was more common (48/49 cases, 158/161 VB) while 3/161 (1.86%) VB had the granular type (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly the intramedullary tuberculomas have specific MR features and can be diagnosed on imaging. It has a typical "target sign" on T2weighted imaging, demonstrating low signal center (caseous material) surrounded by high signal rim (peripheral infective granulation tissue), which helps to differentiate tuberculoma from other intramedullary lesions [10,11]. On intravenous contrast study, these lesions show rounded nodular and ring like peripheral enhancement with nonenhancing center of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…On intravenous contrast study, these lesions show rounded nodular and ring like peripheral enhancement with nonenhancing center of the lesion. If the lesion has a typical appearance on MRI, and if the patient has systemic tuberculosis, diagnosis of tuberculoma can be made easily [9][10][11]. If the patient does not have systemic tuberculosis and has immunocompromised status, MRI features can be atypical as seen in our case and diagnosis can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the best diagnostic tool to show the location, size and number of the lesions [9,10,12,19]. Jena et al [11], in 1991, demonstrated the MRI characteristics of intramedullary tuberculomas as low intensity rings with or without central hyperintensity (because of the varying amount of caseous necrosis) on T2-weighted images and low to isointense rings on T1-weighted images. Rhoton et al [19], in 1988, presented the first known description of MRI of intramedullary spinal cord tuberculomas.…”
Section: T Süzer E Coșkun K Tahta H Bayramoǧlu E Düzcanmentioning
confidence: 99%